OPTIMALISASI PERAN PENGAWAS DALAM MENINGKATKAN MUTU PELAJARAN PENDIDIKAN AGAMA ISLAM - Hayati, Hanida; Syaiful, Muhammad; Khalifaturrahmah, Khalifaturrahmah (Hijri, 2021)
The argument of this article is that in an effort to improve the morals of students and build the character of the young Muslim generation, Islamic religious education subjects play an important role. Therefore, teachers and supervisors must be able to work together, while supervisors need to be more optimal in carrying out supervisory duties. The research method uses a qualitative approach to a literature review with analysis using content analysis. The research finding is that conceptually the supervisor's role is very crucial in improving the quality of education and learning quality. Supervisors greatly contribute to improving the quality of Islamic religious education learning. The author suggests that the government can systematically optimize the role of supervisors by first providing refreshments in the aspects of skills and commitment in carrying out their responsibilities as supervisors of Islamic religious education lessons.Optimization, Supervisor, Islamic Education